2018
DOI: 10.1523/jneurosci.1595-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Single Bursts of Individual Granule Cells Functionally Rearrange Feedforward Inhibition

Abstract: The sparse single-spike activity of dentate gyrus granule cells (DG GCs) is punctuated by occasional brief bursts of 3–7 action potentials. It is well-known that such presynaptic bursts in individual mossy fibers (MFs; axons of granule cells) are often able to discharge postsynaptic CA3 pyramidal cells due to powerful short-term facilitation. However, what happens in the CA3 network after the passage of a brief MF burst, before the arrival of the next burst or solitary spike, is not understood. Because MFs inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 66 publications
0
34
1
Order By: Relevance
“…For instance, the fraction of CA1 neurons recruited during sharp wave ripple mediated replay of behaviourally relevant sequences [23][24][25][26][27][28][29][30] is much higher than the recruitment of GCs in network events. One consequence of the sparseness of network events is that they are predicted to recruit highly constrained CA3 ensembles, both because of the sparse excitatory connectivity of mossy fibers in CA3, and because of the properties of the powerful inhibitory circuits in the CA3 region [31][32][33] . This has been suggested to be important in the capability to store information in CA3, while conserving the pattern separation benefits of the dentate gyrus 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the fraction of CA1 neurons recruited during sharp wave ripple mediated replay of behaviourally relevant sequences [23][24][25][26][27][28][29][30] is much higher than the recruitment of GCs in network events. One consequence of the sparseness of network events is that they are predicted to recruit highly constrained CA3 ensembles, both because of the sparse excitatory connectivity of mossy fibers in CA3, and because of the properties of the powerful inhibitory circuits in the CA3 region [31][32][33] . This has been suggested to be important in the capability to store information in CA3, while conserving the pattern separation benefits of the dentate gyrus 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…This scenario would be consistent with a recently discovered phenomenon at the granule cell to CA3 interneurons synapses. At MF to CA3 interneuron synapses, the passage of an AP burst in granule cells induces a novel form of long‐lasting facilitation in the CA3 inhibitory network (Neubrandt et al., 2018). More precisely, a short burst of granule cell firing specifically maintains MF to interneuron synapses in a state of elevated release probability over several seconds, which will cause an enhanced recruitment of interneuron in response to subsequent granule cell firing (Neubrandt et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, single burst of action potentials in CA3 axons (Schaffer collaterals) can induce robust and stable long-term potentiation at synapses on CA1 pyramidal neurons, provided that the postsynaptic depolarization triggers a dendritic spike 79 . Recent results have also revealed that single bursts in DG granule cells may selectively alter specific functional components of the downstream circuit, such as feedforward inhibitory interneurons 80 .…”
Section: Discussionmentioning
confidence: 99%